Pengaruh PAD, Tenaga Kerja, dan Investasi Terhadap Pertumbuhan Ekonomi di Provinsi Bali - Barimbing, Yesika Resianna; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 5, Mei 2015 (pp. 348 - 607), 2015)
One of important indicators in determine success of economic development is economic growth. The role of government in order to reach succes of development by determine direction of of development policy and to reach development goal will be need a good development planning to realize stabil economic growth in order to improve public prosperity by improve local origin income, employment and investment. This study aims to find out the effect simultaneously and partially the local origin income, employment and investment toward economic development. Source of data was secondary data by using panel data that consist of time series data during five years and cross section data with nine regency/city that result 45 observation. Analysis technique to problem solving this study was multiple regression linear. The result showed that simultaneously local origin income, employment and investment have significant effect toward economic development in Bali. Partially local origin income, employment and investment have significant effect toward economic development in Bali province, while investment have positive effect but it not significant.
Keywords: pertumbuhan ekonomi; PAD; tenaga kerja; Investasi